Climate change adaptation strategies of cocoa farmers in the Wassa East District: Implications for climate services in Ghana - Enoch A. Kosoe; Abubakari Ahmed (Climate Services, 2022)
Studies have generally shown that climate change has tremendous impacts on cocoa productivity. Although there is an increasing proliferation of studies on adaptation strategies of cocoa farmers, many of the studies are not linked to climate services that provide information to help ensure climate smart decision-making among cocoa farmers. This study investigates the perception and adaptation strategies of cocoa farmers to draw insights into climate services necessary for adaptation. Through a semi-structured questionnaire survey of 150 cocoa farming households and Focus Group Discussions, the study found that key adaptation strategies include changing planting dates, diversification to non-farm activities, planting improved cocoa varieties, crop diversification, and tree planting. Age and information seeking behaviour of farmers have positive influence on access to climate services which serves as a basis for these adaptation strategies. The existing climate services are not comprehensive enough to cover the wide array of adaptation needs of farmers. Current services focus on only dissemination of rainfall and temperature information through radio and television without providing information on other adaptation needs such as planning and harvesting dates. The findings suggest that there is a need for scaling up access to climate services in areas of planting services and crop improvement through zero literacy devices if cocoa farmers’ adaptation to climate impacts are to be addressed.